BEING STRONGER IN NEW GLOBAL SUPPLY CHAIN AFTER THE PANDEMIC: SEEKING TO INCREASE FOREIGN TRADE VOLUME AND EMPLOYMENT SIMULTANEOUSLY IN TURKEY ECONOMY - Yunus Emre Aydınbaş; İlkay Güler (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study is intended to discuss turning a broken global supply chain into an opportunity by Turkey in post-COVID-19 period and the possibility to be an alternative to China in the sectors in which Turkey is more advantageous and solution seeking to repair the employment structure which has been damaged in pandemic process. Partial direct backward linkages coefficients of both countries were calculated and Leontief similarity test and Spearman correlation test were applied to the obtained coefficients, and the results of both tests were evaluated together. As a result of the analysis, sectors having the advantage of Turkey's foreign trade is as follows: “manufacture of food products”, “manufacture of textiles”, "manufacture of other non-metalic mineral products", "construction" “manufacture of articles of straw and plaiting materials” and “manufacture of computer, electronic and optical products, manufacture of electrical equipment”. The activities of the first 4 of these sectors are among the 6 activities which were published by TOBB and they were most affected by the Covid-19 outbreak and closed down.electronic and optical products, manufacture of electrical equipment”.